2019
DOI: 10.1111/1365-2664.13375
|View full text |Cite
|
Sign up to set email alerts
|

Compounding human stressors cause major regeneration debt in over half of eastern US forests

Abstract: 1. The future of temperate forests in the face of global change and anthropogenic stressors remains uncertain. The regeneration stage, which is a critical bottleneck for many organisms, is a key indicator of forest health, future canopy composition and forest adaptive capacity.2. In trees, seemingly healthy forests can be at long-term risk due to insufficient juveniles to replace them (regeneration failure), or compositional differences between juveniles and adults (regeneration mismatch). We propose 'regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
2
28
1
Order By: Relevance
“…Despite differences among locations and years, our study demonstrated that deer browse was the overwhelming threat to growth of unprotected Q. rubra seedlings, with rodents and other factors relatively unimportant (Figure ), confirming our second hypothesis. These results align well with results of regional studies (Kelly, ; Miller & McGill, ) and the demographic model for Q. lobata in California (Davis et al, ), all indicating that after successful germination, seedlings are unable grow and transition to larger saplings under high deer browse pressure. This browse (and rodent attack) occurred rapidly in spring and early summer, and we would expect the same to occur for naturally germinating oaks.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Despite differences among locations and years, our study demonstrated that deer browse was the overwhelming threat to growth of unprotected Q. rubra seedlings, with rodents and other factors relatively unimportant (Figure ), confirming our second hypothesis. These results align well with results of regional studies (Kelly, ; Miller & McGill, ) and the demographic model for Q. lobata in California (Davis et al, ), all indicating that after successful germination, seedlings are unable grow and transition to larger saplings under high deer browse pressure. This browse (and rodent attack) occurred rapidly in spring and early summer, and we would expect the same to occur for naturally germinating oaks.…”
Section: Discussionsupporting
confidence: 87%
“…Despite differences among locations and years, our study demonstrated that deer browse was the overwhelming threat to growth of unprotected Q. rubra seedlings, with rodents and other factors relatively unimportant ( Figure 6), confirming our second hypothesis. These results align well with results of regional studies (Kelly, 2019;Miller & McGill, 2019) Note: Initial vegetation height was not significant and dropped from best models. The null model was the best model predicting unknown mortality (for 2010 and 2011) and rodent attack (2011).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations